2016
DOI: 10.18433/j31s53
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity of Human Cytochrome P450 (CYP) 2C Subfamily and Effect of Azole Antifungal Agents on CYP2C8

Abstract: -PURPOSE: The metabolic activities of aminopyrine N-demethylation and tolbutamide methylhydroxylation by the human hepatic cytochrome P450 (P450 or CYP) 2C subfamily were compared and the effects of azole antifungal agent on the drug-metabolizing activity of CYP2C8 were investigated. METHODS: Aminopyrine N-demethylation and tolbutamide methylhydroxylation by CYP2C8, CYP2C9, and CYP2C19 were determined by the previous reported methods. The effects of five azole antifungal agents, fluconazole, itraconazole, keto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…An increasing amount of a cross-reacting CYP2C protein was observed in the liver of PB-treated cattle, thus partially confirming transcriptional results (i.e., CYP2C31 and CYP2C42 ). Bovine CYP2C-dependent catalytic activities were evaluated by using the broad substrates aminopyrine [ 95 , 120 , 121 ], chlorpheniramine [ 122 , 123 ], and 7-MFMC [ 94 , 101 , 123 ]. Phenobarbital significantly increased the in vitro metabolism ( N- demethylation) of the abovementioned substrates, and especially of 7-MFMC.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing amount of a cross-reacting CYP2C protein was observed in the liver of PB-treated cattle, thus partially confirming transcriptional results (i.e., CYP2C31 and CYP2C42 ). Bovine CYP2C-dependent catalytic activities were evaluated by using the broad substrates aminopyrine [ 95 , 120 , 121 ], chlorpheniramine [ 122 , 123 ], and 7-MFMC [ 94 , 101 , 123 ]. Phenobarbital significantly increased the in vitro metabolism ( N- demethylation) of the abovementioned substrates, and especially of 7-MFMC.…”
Section: Discussionmentioning
confidence: 99%
“…Because N-demethylation of 13 C-aminopyrine has been shown to be the rate-limiting step, it has been assumed that the ABT reflects the activity of the cytochrome P450-dependent mono-oxygenase system and gives a global assessment of this system. It has been demonstrated that the N-demethylation of aminopyrine is catalyzed most efficiently by CYP2C19 and CYP2C8, followed by CYP2D6, 2C18, 1A2 and 2B6; and to a lesser extent by CYP2C9, 2A6, 1A1 and 3A4 [5,6]. Aminopyrine metabolism is mostly dependent on hepatic metabolic capacity (functional hepatic mass) rather than on portal blood flow [7].…”
Section: Introductionmentioning
confidence: 99%
“…Their mechanism of action occurs by inhibiting the enzyme 14α-demethylase (14 DM), an important cytochrome P-450 enzyme in the ergosterol biosynthesis route, which catalyzes the oxidative removal of the 14α-methyl group from lanosterol (ZHANG et al, 2016;NIWA;IMAGAWA, 2016;SUI et al, 2017). Azole, bound to the active site of this enzyme, competes with the substrate for binding).…”
Section: Introductionmentioning
confidence: 99%